Performance appraisal : one more time - Drake, John D. (Crisp Pub. Menlo ParkUS, 1997)
Reviews performance appraisal systems in current use and advances reasons for failure. Analyses options for measuring performance and examines the use of objectives to improve performance. Presents a model for establishing a performance appraisal system which incorporates 8 conditions, and is viewed as an on-going process and not an annual event. Focuses on manager/employee discussions on: work planning; progress toward established goals; and summary appraisal at the end of the rating cycle. Discusses the nature of useful feedback - specific, immediate, descriptive, and two-way. Provides a six-step model for providing negative feedback to employees; as well as step-by step models for conducting reviews and summary appraisals.